2006
DOI: 10.1002/adsc.200505345
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalysed Direct Couplings of Indoles and Pyrroles with 1,3‐Dicarbonyl Compounds

Abstract: Abstract:The gold-catalysed direct couplings of indoles 1 and pyrroles 5 with 1,3-dicarbonyls 2 is described. This new method for C À C bond formation allows high functional group tolerance, regioselectivity, and scope under relatively mild conditions. Moreover, the 3-alkenylindoles 3 can be readily available through gold-catalysed sequential cyclization/alkenylation reaction of 2-alkynylanilines derivatives 4 with 1,3-dicarbonyls 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 59 publications
3
32
0
1
Order By: Relevance
“…Metal activation of 1,3‐dicarbonyl compounds towards the reaction with indoles has been introduced ten years ago using Au III salts, and anhydrous FeCl 3 (Scheme ) . Linear 1,3‐diketones and β‐ketoesters as well as 1,3‐cycloakanediones can be used to afford the corresponding alkenylated indoles.…”
Section: Addition–elimination Of Indoles To Carbonyl Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal activation of 1,3‐dicarbonyl compounds towards the reaction with indoles has been introduced ten years ago using Au III salts, and anhydrous FeCl 3 (Scheme ) . Linear 1,3‐diketones and β‐ketoesters as well as 1,3‐cycloakanediones can be used to afford the corresponding alkenylated indoles.…”
Section: Addition–elimination Of Indoles To Carbonyl Derivativesmentioning
confidence: 99%
“…Metal activation of 1,3-dicarbonyl compounds towards the reactionw ith indoles hasb een introduced ten years ago using Au III salts, [180] and anhydrous FeCl 3 (Scheme 90). [181] Linear1 ,3diketones and b-ketoesters as well as 1,3-cycloakanediones can be used to afford the corresponding alkenylated indoles.T he utilization of FeCl 3 as catalysts eems more effective than Au III derivatives but the latter metal shows ah igher versatility since the reaction can also be appliedt oatandemp rocess starting from remote precursorso ft he indole ring such as 2-alkynyl Scheme87.…”
Section: C-3 Alkenylationsmentioning
confidence: 99%
“…This latter pathway (Path A, Scheme ), involving a dual role of the catalyst as both π‐ and σ‐activator, was suggested to be more likely. In related experiments, application of gold(III) catalysis accomplished a sequential cyclization/alkenylation reaction of 2‐alkynylanilines with 1,3‐dicarbonyls (Scheme ) 53…”
Section: Gold‐catalyzed Sequential Reactions Of 2‐alkynylanilinesmentioning
confidence: 99%
“…Gold catalysts have also been used in domino sequences starting from o -alkynylanilines. Arcadi and Marinelli reported that gold-catalyzed cyclization of 2-alkynylanilines can be followed by 1,4-addition to enones [1516], iodination [17] or reaction with 1,3-dicarbonyl compounds [18]. Perumal recently demonstrated that aldehydes and nitroalkenes can be used as electrophilic partners [1920].…”
Section: Introductionmentioning
confidence: 99%